Claudin‐7 increases chemosensitivity to cisplatin through the upregulation of caspase pathway in human NCI‐H522 lung cancer cells. Issue 5 (29th March 2013) - Hoggard, John; Fan, Junming; Lu, Zhe; Lu, Qun; Sutton, Leonard; Chen, Yan‐Hua
<x xml:space="preserve">Abstract</x> Claudins are a family of tight junction (TJ) integral membrane proteins that play a crucial role in maintaining cell polarity, adhesion, and paracellular permeability. Changes in expression levels of claudin proteins have been associated with human lung cancer. Previously, we have reported that claudin‐7 expression is significantly downregulated in human lung carcinomas. To investigate the role of claudin‐7 in lung cancer cells after anti‐cancer drug treatments, we transfected claudin‐7 cDNA into human NCI‐H522 lung cancer cells, which have no detectable expression of claudin‐7 protein. Flow cytometry analysis demonstrated that cells transfected with claudin‐7 had a significantly higher percentage of cell apoptosis when compared to that of vector transfected cell population. The cell viability assayed by MTT and Annexin V was significantly decreased and cell apoptosis was dramatically increased in claudin‐7 transfected cells compared to that of vector transfected cells after cisplatin treatment. Cisplatin is an anti‐cancer drug clinically used to treat tumors in several tissues including lung tumors. Most importantly, after cisplatin treatment, the expression levels of cleaved caspase‐3, ‐8, and poly adenosine 5′‐diphosphate ribose polymerase (PARP) were much higher in claudin‐7 transfected cells than in control cells. Furthermore, using the site‐directed mutagenesis approach, we identified that claudin‐7 was phosphorylated at serine 204 by protein kinase C. Non‐phosphorylated claudin‐7 mutant showed increased cell viability, suggesting that phosphorylation increases chemosensitivity to cisplatin treatment. We concluded that claudin‐7 expression in H522 lung cancer cells increases chemosensitivity to cisplatin through the increased activation of caspase pathway.